Expressions of Austronesian Thought and Emotions - J. Fox, James (ANU Press, 2018)
This collection of papers is the seventh volume in the Comparative Austronesian series. The papers in this volume focus on societies from Sumatra to Melanesia and examine the expression and patterning of Austronesian thought and emotions.